Threshold for defining fever varies with age, especially in children: A multi‐site diagnostic accuracy study - Rajesh Kasbekar; Aftab Naz; Lorenzo Marcos; Yingjie Liu; Kristine Hendrickson; James C. Gorsich; Matt Baun (Wiley, 2021)
Abstract Aim The American Academy of Pediatrics and the European Centre for Pediatric and Adolescent Medicine guideline define fever as a temperature >38.0°C for all ages and recommend use of rectal thermometers in children <3 years. Based on new literature, this definition of fever using a fixed threshold of 38.0°C needs to be re‐examined. Design A multi‐site diagnostic accuracy study was conducted to compare an "age‐based" threshold model with a "fixed" threshold over 38.0°C on a total of 894 patients of which 373 were ill. Methods The "age‐based" and "fixed" threshold fever determinations were then compared to a clinical categorization ("well" or "ill") conducted by a clinician through a comprehensive examination. Results The sensitivity and accuracy for the age‐based thresholds were found to be superior to the fixed thresholds in all ages and current ear thermometers were found equivalent to rectal thermometers in infants <6 months.